2005
DOI: 10.1007/s10404-005-0057-4
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating DNA molecules in nanofluidic channels

Abstract: Nanofluidic channels of $40·60 nm (width · depth) were fabricated with focused ion beam (FIB) milling instrument on a silicon nitride (Si 3 N 4 ) film. Stained k-phage DNA molecules were driven into these open channels by capillary force and observed with fluorescence microscopy. The movements of DNA molecule in these channels were discussed. These sub-100 nm scale channels may be useful in studying single biomacromolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Although the channel surface properties (Kirby and Hasselbrink 2004a, b;Herr et al 2000) affected the performance of the microchannels and controlled the electroosmotic flow, resultant electric fields and velocity fields were of interest for fundamental studies. in separating the biochemical samples using electrophoresis (Fujimura et al 2003), in manipulating neuron outgrowth or in working with bio-sensor applications (Lo et al 2004), in manipulating DNA molecules (Wang et al 2006), in enhance mixing for bio-sample reactions (Yang et al 2006), in detecting glucose (Tseng et al 2004) and in cooling of microelectronics (Nilson et al 2006). However, very few fundamental studies have been reported on open microchannel flow systems driven by surface tension.…”
Section: Introductionmentioning
confidence: 98%
“…Although the channel surface properties (Kirby and Hasselbrink 2004a, b;Herr et al 2000) affected the performance of the microchannels and controlled the electroosmotic flow, resultant electric fields and velocity fields were of interest for fundamental studies. in separating the biochemical samples using electrophoresis (Fujimura et al 2003), in manipulating neuron outgrowth or in working with bio-sensor applications (Lo et al 2004), in manipulating DNA molecules (Wang et al 2006), in enhance mixing for bio-sample reactions (Yang et al 2006), in detecting glucose (Tseng et al 2004) and in cooling of microelectronics (Nilson et al 2006). However, very few fundamental studies have been reported on open microchannel flow systems driven by surface tension.…”
Section: Introductionmentioning
confidence: 98%
“…Many areas employ multiphase droplet-based microfludics (Shui et al 2007;Gunther and Jensen 2006), including inkjet printers (van Dam and Le Clerc 2004), systems for separation of biochemical samples (Fujimura et al 2003), manipulation of biomolecules (Lo et al 2004), bio-sensing (Wang et al 2006), single cell analysis (Yong et al 2010), enhanced mixing for bio-sample reactions (Yang et al 2006), biomolecular detection (Tseng et al 2004), drug delivery devices (Chung et al 2008), dairy analysis (Skurtys and Aguilera 2008), microelectronic cooling (Nilson et al 2006), explosives detection (Piorek et al 2007), bubble computing (Prakash and Gershenfeld 2007), interfacial tension measurement (Xu et al 2008), and analysis of emulsions, foams, and bubble coalescence (Kralj et al 2005). As general characteristics, the droplets should be as stable, monodisperse, reproducible, and controllable as possible.…”
Section: Introductionmentioning
confidence: 99%
“…DNA separation is an essential operation in many genetic engineering processes and is commonly performed when executing biochemical and biological analyses (Bown and Meinhart 2006;Das et al 2006;Gutsche et al 2006;Szantai and Guttman 2006;Wang et al 2006Liu et al 2007Llopis et al 2007;Ohashi et al 2007;Prakash and Kaler 2007;Sun et al 2007). However, the conventional slab-gel DNA separation method has a number of drawbacks, including a long separation time, an excessive sample consumption and a low separation efficiency.…”
Section: Introductionmentioning
confidence: 99%